Elevated concentrations of serum matrix metalloproteinase-2 and -9 and their associations with circulating markers of cardiovascular diseases in chronic arsenic-exposed individuals. Issue 1 (December 2015) - Islam, Md; Mohanto, Nayan; Karim, Md; Aktar, Sharmin; Hoque, Md; Rahman, Atiqur; Jahan, Momotaj; Khatun, Rabeya; Aziz, Abdul; Salam, Kazi; Saud, Zahangir; Hossain, Mostaque; et al.
Abstract Background Cardiovascular diseases (CVDs) and cancers are the major causes of chronic arsenic exposure-related morbidity and mortality. Matrix metalloproteinase-2 (MMP-2) and −9 (MMP-9) are deeply involved in the pathogenesis of CVDs and cancers. This study has been designed to evaluate the interactions of arsenic exposure with serum MMP-2 and MMP-9 concentrations especially in relation to the circulating biomarkers of CVDs. Methods A total of 373 human subjects, 265 from arsenic-endemic and 108 from non-endemic areas in Bangladesh were recruited for this study. Arsenic concentrations in the specimens were measured by inductively coupled plasma mass spectroscopy (ICP-MS) and serum MMPs were quantified by immunoassay kits. Results Serum MMP-2 and MMP-9 concentrations in arsenic-endemic population were significantly (p  < 0.001) higher than those in non-endemic population. Both MMPs showed significant positive interactions with drinking water (r s  = 0.208, p  < 0.001 for MMP-2;r s  = 0.163, p  < 0.01 for MMP-9), hair (r s  = 0.163, p  < 0.01 for MMP-2;r s  = 0.173, p  < 0.01 for MMP-9) and nail (r s  = 0.160, p  < 0.01 for MMP-2;r s  = 0.182, p  < 0.001 for MMP-9) arsenic of the study subjects. MMP-2 concentrations were 1.02, 1.03 and 1.05 times, and MMP-9 concentrations were 1.03, 1.06 and 1.07 times greater for 1 unit increase in log-transformed water, hair and nail arsenic concentrations, respectively, after adjusting for covariates (age, sex, BMI, smoking habit and hypertension). Furthermore, both MMPs were increased dose-dependently when the study subjects were split into three (≤10, 10.1-50 and > 50 μg/L) groups based on the regulatory upper limit of water arsenic concentration set by WHO and Bangladesh Government. MMPs were also found to be significantly (p  < 0.05) associated with each other. Finally, the concentrations of both MMPs were correlated with several circulating markers related to CVDs. Conclusions This study showed the significant positive associations and dose–response relationships of arsenic exposure with serum MMP-2 and MMP-9 concentrations. This study also showed the interactions of MMP-2 and MMP-9 concentrations with the circulating markers of CVDs suggesting the MMP-2 and MMP-9 -mediated mechanism of arsenic-induced CVDs.